Le ricette per gli occhi nel ms. 1408 della Biblioteca Statale di Lucca (Carte Romanze, 2020)
In this paper I analyze a case-study about a little group of medical recipes content in a XV century manuscript (Lucca, Biblioteca Statale, ms. 1480). The receptarium contains mostly recipes for the eyes care and maybe is a book belonged to a monk who lived in Tuscany in the XV century. I propose, therefore, to consider the existence of a third category of receptaria (monastic receptaria) in addition to domestic and professional ones already identified and described by Lluís Cifuentes.